Apigenin and its derivatives in breast cancer prevention and therapy: a review on bioavailability and recent developments - Ghumika Pandita; Disha Mittal; Piyush Kashyap; Wing-Fu Lai; Naveen Kumar; Rahul Mehra; Mohd Adnan; Syed Amir Ashraf (Phytomedicine Plus)
Breast cancer has emerged as the most prevalent cancer and the leading contributor to cancer-related fatalities among women worldwide. The treatments directed at primary breast tumors have significantly advanced; however, those aimed at elusive micro-metastases have shown comparatively lower effectiveness. In this regard, bioactive compounds specifically flavonoids derived from plants have gained worldwide attention due to their potential in cancer chemoprevention and treatment. Among them, Apigenin (APN), a flavonoid rich in several fruits, vegetables, and herbs, has been studied extensively for its possible role in treating and preventing breast cancer. This review discusses APN and its derivatives anticancer activity, including their molecular mechanisms, therapeutic effects, and latest developments in improving bioavailability. The anti-proliferative, pro-apoptotic, anti-inflammatory, and antimetastatic activity of APN are mediated through signal transduction pathways such as PI3K/Akt, MAPK, and NF-κB. APN found to initiates apoptosis, suppresses cell proliferation, prevents cell cycle progression, and inhibits metastasis and angiogenesis in different breast cancer models, including triple-negative breast cancer (TNBC). Even though preclinical studies of APN are promising but the clinical use of it is limited due to its poor solubility, low bioavailability, fast metabolism, and low absorption. To address these limitations, researchers have created derivatives (such as methylated or glycosylated versions) with enhanced stability and activity, and nanoformulations such as liposomes, lipid nanoparticles, and micelles for improved solubility, degradation resistance, and targeted delivery. As a results, APN and its derivatives are highly promising for breast cancer prevention and treatment. More research on delivery systems and modifications of their structures is critical for improving their clinical effectiveness. Thus, the focus of this review is also on recent mechanisms of action, bioavailability problems, and formulation approaches for eventual clinical applications. The future needs to focus on clinical trials and combination therapy in order to maximize their therapeutic potential.